The discourse on the eighth and ninth VI,6: 52,1 - 63,32 (TDOTEAN) - Dirkse, Peter A. (BrillOnline Reference Works, 2012)
In the MS the text is well preserved in the bottom and mid-page areas throughout. However the text at the top of every page is damaged, although the condition steadily improves as one moves through the tractate